2021
DOI: 10.1097/qai.0000000000002803
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy Among PLWH in South India: Implications for Vaccination Campaigns

Abstract: Background: The global effort to end the Severe Acute Respiratory Syndrome - Coronavirus 2 pandemic will depend on our ability to achieve a high uptake of the highly efficacious vaccines in all countries. India recently experienced an unprecedented transmission surge, likely fueled by a premature reopening, the highly transmissible delta variant, and low vaccination rates. Indian media have reported high degrees of vaccine hesitancy, which could interfere with efforts to prevent future surges, makin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 22 publications
3
27
1
3
Order By: Relevance
“…We next examined whether the CoronaVac vaccine can elicit a similar humoral response in PLWH compared with HC. Our results supported recent reports that humoral responses elicited by COVID-19 vaccines are comparable in PLWH and HC within 4 weeks [23][24][25], and we further demonstrated a similar outcome over a longer period of time, supporting the current advice for PLWH to be immunized with COVID-19 vaccines. In previous studies, PLWH with CD4 + T cells counts <200 cells/µL have shown diminished SARS-CoV-2 antibody production after acute infection [34], as well as blunted immune responses to multiple vaccine types [35].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We next examined whether the CoronaVac vaccine can elicit a similar humoral response in PLWH compared with HC. Our results supported recent reports that humoral responses elicited by COVID-19 vaccines are comparable in PLWH and HC within 4 weeks [23][24][25], and we further demonstrated a similar outcome over a longer period of time, supporting the current advice for PLWH to be immunized with COVID-19 vaccines. In previous studies, PLWH with CD4 + T cells counts <200 cells/µL have shown diminished SARS-CoV-2 antibody production after acute infection [34], as well as blunted immune responses to multiple vaccine types [35].…”
Section: Discussionsupporting
confidence: 92%
“…This situation is also observed in other vaccine inoculations, such as vaccines for influenza, human papillomavirus, and hepatitis B virus [21][22][23]. In the previous studies, the rates of vaccine hesitancy among PLWH towards the COVID-19 vaccine ranged from 28.7% to 54% [12,[24][25][26]. Individually, vaccine hesitancy rates in PLWH were highest in black Americans (54%) [25] and were lowest in the French PLWH (28.7%) [12].…”
Section: Discussionmentioning
confidence: 63%
“…Our study contributes to the limited literature on vaccine hesitancy among the nationwide sample of PWH living in the U.S., revealing most participants having some levels of hesitancy concerning COVID-19 vaccination. Previously reported vaccine hesitancy rates range from 22% to 42.4% among the adult American population [ 5 , 6 , 7 , 31 ] and 27.5% to 38.4% among PWH across various settings [ 32 , 33 , 34 ]. It is troubling that the vaccine hesitancy among PWH in our sample fell on the higher side of these ranges, as the pandemic adversely impacts HIV care with increasing loss to follow-up or disengagement [ 8 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…These included concerns about the efficacy, safety, and side effects of the vaccine. Although COVID-19 vaccine hesitancy among PWH across the globe is still advancing, multiple studies have already highlighted similar findings across various settings [ 32 , 33 , 34 ]. This finding becomes especially relevant in the context of the reported mistrust in COVID-19 or COVID-19 vaccine information sources, which has also been correlated with vaccine hesitancy [ 8 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination hesitancy may be a barrier to restarting clinical research in PLWH [61,62]. Reasons for hesitancy should be explored and the protective effect of vaccination, including reassuring vaccine safety and efficacy data, shared.…”
Section: Ethics Of Proceeding With Those Not Willing To Receive a Cov...mentioning
confidence: 99%